2022
DOI: 10.1186/s12888-022-03980-6
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, stress and intentions to leave work in New Zealand psychiatrists; a mixed methods cross sectional study

Abstract: Background Demand for mental health services in New Zealand and internationally is growing. Little is known about how psychiatrists are faring in this environment. This study aimed to investigate wellbeing of psychiatrists working in the public health system in New Zealand, identify the main risk factors for work-related stress, gauge perceptions of how workload has changed over time, assess job satisfaction and whether individuals intend or desire to leave their work. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
4
8
0
Order By: Relevance
“…Some individual factors appear unique to the podiatry profession, while others, such as personality [ 29 ] and younger age [ 29 , 30 ], have been shown to be associated with burnout in other healthcare practitioners. Although this study did not explore whether burnout leads to practitioner turnover, it did reveal an association with an intention to leave the profession, aligning with findings in other healthcare fields [ 31 , 32 , 33 ]. Further exploration of this relationship in future podiatry workforce research is warranted, as early career burnout by younger podiatrists may lead to an older workforce distribution [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 81%
“…Some individual factors appear unique to the podiatry profession, while others, such as personality [ 29 ] and younger age [ 29 , 30 ], have been shown to be associated with burnout in other healthcare practitioners. Although this study did not explore whether burnout leads to practitioner turnover, it did reveal an association with an intention to leave the profession, aligning with findings in other healthcare fields [ 31 , 32 , 33 ]. Further exploration of this relationship in future podiatry workforce research is warranted, as early career burnout by younger podiatrists may lead to an older workforce distribution [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 81%
“…These results were comparable with our earlier sample of NZ psychologists in 2021 ( Kercher and Gossage, 2023 ), so measurement errors are unlikely—psychologists have repeatedly reported elevated distress. Similar difficulties were reported for frontline HCPs ( Bell et al, 2021 ) and psychiatrists in NZ during the pandemic ( Chambers and Frampton, 2022 ), but with different measures preventing direct comparisons.…”
Section: Discussionmentioning
confidence: 58%
“…Encouragingly, our respondents reported good average rates of compassion satisfaction. Additionally, more than 90% reported that they had no intention to leave the profession soon (in contrast with NZ psychiatrists, nearly half of whom reported intention to leave, Chambers et al, 2022 ). Psychologists report finding their work rewarding and satisfying, reflected in the reported sense of purpose and reward both here and internationally during the pandemic ( British Psychological Society, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a rational explanation for this, in that immigrant workers’ mental health declines as a result of the stress brought about by growing workloads and low levels of reward in host countries [ 70 ]. Work-related stress has long been recognized as a key risk factor for migrant workers’ mental health [ 71 ]. An interesting finding from a study of interviews with foreign care workers in Japan is that completing paper care records and other documents in Japanese is also seen as a heavy workload that can lead to burnout [ 7 ].…”
Section: Discussionmentioning
confidence: 99%